Morphological characteristics of lateral branches of human basilar artery - Gajanin Vesna; Sladojević Igor; Šarović-Vukajlović Mirka; Gajanin Radoslav; Ninković-Baroš Đuka; Krivokuća Božo (Vojnosanitetski Pregled)
Background/Aim. Lateral branches of basilar artery mostly supply pons and cerebellum. The aim of this study was to determine the morphological characteristics of lateral branches and side branches of the individual lateral branches of human basilar artery. Methods. The research was done on 25 anatomical specimens of adult brainstems, both sexes, previously fixed by immersion in a 10% formalin. Microdissection and precise measurements of caliber and length of the basilar artery were done under the stereolupe MBS-9 by the ocular micrometer. Results. A number of lateral branches was 9 on both sides, and the number of side branches of the individual lateral branch of basilar artery ranged from 0 to 4. The average diameter of side branches on both sides was 0.15 mm while the average length on the left side was 4.31 mm and 4.06 mm on the right. Side braches on the left side of the basilar artery most commonly penetrated pons and postpontine fossa (29.82% each) and rarely the area of middle cerebellar pedicle (1.74 %). On the right side, side branches most commonly penetrated pons (35.29%), and rarely the areas of inferior and middle cerebellar pedicle (1.96% each). Conclusion. Maintrunk of basilar artery gives an equal number of lateral branches on both sides. On average, every lateral branch gives 2 side branches. The most common site of descent of the side branches is pons, while the rarest one was cerebellar pedicle.